Implementasi Pendekatan Communicative Learning dalam Meningkatkan Maharah Kalam di Marhalah Wustho Lembaga Pengembangan Bahasa Asing Nurul Jadid - Wijaya, Mualim; Trisnawati, Ayu (AS-SABIQUN, 2025)
Intermediate level students at LPBA Nurul Jadid have low speaking skills, because students have difficulty expressing themselves by speaking Arabic both in formal and non-formal situations. When speaking with administrators, upper and intermediate levels, for example, students look nervous, unclear pronunciation, flat intonation and less interactive language. This study aims to describe how the communicative learning approach to improve Arabic speaking skills and its application in LPBA Nurul Jadid women. The communicative learning approach is an approach whose main priority is speaking Arabic or using Arabic as a language of communication in interacting with one another, the nature of language itself is speaking or saying, so the purpose of the communicative learning approach is to provide students with the information, practice, and experience needed for the benefit of communication. With the communicative learning approach, students will be taught little by little a habit in Arabic. In principle, the communicative learning approach is very important for students in improving their maharah kalam because it will train their proficiency in speaking Arabic, this research uses qualitative research methods, data collection is carried out by observation, interviews and documentation, meaning that information from various sources / informants is presented in the form of words and language in a special context that is natural. With this approach, students will be easy to speak Arabic easily and fluently.